2013
DOI: 10.2174/1381612811319370004
|View full text |Cite
|
Sign up to set email alerts
|

Design and In vitro Validation of Multivalent Dendrimer Methotrexates as a Folate-targeting Anticancer Therapeutic

Abstract: Design of cancer-targeting nanotherapeutics relies on a pair of two functionally orthogonal molecules, one serving as a cancer cell-specific targeting ligand, and the other as a therapeutic cytotoxic agent. The present study investigates the validity of an alternative simplified strategy where a dual-acting molecule which bears both targeting and cytotoxic activity is conjugated to the nanoparticle as cancer-targeting nanotherapeutics. Herein we demonstrate that methotrexate is applicable for this dual-acting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Thus, MTX is unable to cross the cell membrane passively unless being uptaken in an active mechanism which is mediated by cell surface proteins like folate receptor and reduced folate carrier. 21 Thus, MTX may be used as not only an anticancer drug but also a potential targeting ligand. [22][23][24] Therefore, in this manuscript, based on the findings from previous studies, 3,4 we have further elaborated on the mechanism of the affinity between F127/ P105-MTX and folate receptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, MTX is unable to cross the cell membrane passively unless being uptaken in an active mechanism which is mediated by cell surface proteins like folate receptor and reduced folate carrier. 21 Thus, MTX may be used as not only an anticancer drug but also a potential targeting ligand. [22][23][24] Therefore, in this manuscript, based on the findings from previous studies, 3,4 we have further elaborated on the mechanism of the affinity between F127/ P105-MTX and folate receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, it was suggested that although MTX has relatively lower affinity to folate receptor compared with FA (K D =~20-100 nM vs 31,32 MTX-conjugated micelles might bind to folate receptor through polyvalent interaction as reported recently. 21,33,34 cellular uptake mechanism of FITclabeled mixed micelles in KBv cells…”
mentioning
confidence: 99%
“…Although FRα-mediated transport of MTX is unlikely to be of clinical importance, 26 it may be involved in the effects produced by MTX nanocarriers. 5 However, neither anti-FRα antibody ( Figure S1B) nor folic acid inhibited L-MTX-DG binding to cells. Notably, the tested carcinoma cells do not belong to lineages highly expressing FR, and an increase in the receptor expression by the privation of vitamin B9 in cultural medium was not endeavored.…”
Section: Discussionmentioning
confidence: 93%
“…alekseeva et al polyamide dendrimers, 5 polymer nanogels, 6 nanostructured carriers composed of triglycerides and surfactants, 7 quantum dots, 8 polyethylene glycol (PEG)-phospholipid micelles, 9 and liposomes. 10,11 Most of these carriers have insufficient drugloading capacity.…”
mentioning
confidence: 99%
“…Additionally, the tumor selectivity of nanoparticles can be fur- 69 ther enhanced in an active manner by employing a targeting moi-70 ety [7]. The surface of nanoparticles can be functionalized with 71 specific ligands that target corresponding cellular receptors over-72 expressed in cancer cells [8]. Among numerous cell surface recep- 73 tors that are present on malignant cells, HER-2 a receptor tyrosine 74 kinase presents itself as an interesting target for achieving tumor 75 specific drug delivery.…”
mentioning
confidence: 99%